LEVERAGING EDUCATIONAL TECHNOLOGY: STATISTICAL EVIDENCE ON AI'S ROLE IN MATHEMATICS LEARNING OUTCOMES - Andrini, Vera Septi; Hidayati, Umi; Etika, Erdyna Dwi (Edukasi: Jurnal Pendidikan, 2025)
This study aims to analyze the role of Artificial Intelligence (AI) and Learning Analytics (LA) in improving mathematics learning outcomes in higher education. An explanatory sequential mixed-methods design was employed, beginning with quantitative data collection through pre-tests and post-tests, followed by qualitative analysis. Research instruments included a mathematics achievement test, semi-structured interview guidelines, observation sheets, and a student engagement questionnaire. The study involved 120 students and 6 mathematics lecturers. The results showed that the integration of AI (β = 0.624) and LA (β = 0.312) significantly accounted for 72.8% of the variance in students' mathematics achievement. The integrated system is capable of analyzing cognitive, affective, and psychomotor aspects with a prediction accuracy of up to 94% and identifying 89% of learning issues before examinations. These findings provide an empirical foundation for developing effective, adaptive, and flexible mathematics learning systems in higher education.